Unveiling the role of TRPA1 in cardiovascular health and disease: a mini review - Gellani, Islam; Qian, Chunqi; Ma, Shuangtao (Frontiers in Cardiovascular Medicine, 2024)
The transient receptor potential ankyrin 1 (TRPA1) ion channel has emerged as significant regulators of cardiovascular physiology and pathology. TRPA1 is a non-selective cation channel permeable to calcium ions. A unique feature of the channel is its function as a sensor of various temperature, chemical and mechanical stimuli, while it can also be activated by endogenous inflammatory mediators and reactive oxygen species. Over the last two decades, much progress has been made in illuminating the role of TRPA1 in the regulation of cardiovascular physiology and pathophysiology in addition to its important function in pain sensation. This review provides a comprehensive analysis of recent studies investigating the involvement of TRPA1 channels in various cardiovascular diseases, including myocardial infarction, ischemia-reperfusion injury, myocardial fibrosis, and response to environmental toxins. We discuss the diverse roles of TRPA1 channels in cardiac pathology and highlight their potential as therapeutic targets for cardiovascular disorders. Moreover, we explore the challenges and opportunities linked with targeting TRPA1 channels for treating cardiovascular diseases, alongside future research directions.